KARAKTERISTIK ENKAPSULAT PEWARNA FUNGSIONAL DARI EKSTRAK SELADA LAUT (Ulva lactuca L) PADA PERLAKUAN PERBANDINGAN GELATIN DAN MALTODEKSTRIN - Fridayana, I Wayan Eko; Wrasiati, Luh Putu; Ganda Putra, G.P (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 6 No 4 (2018): Desember, 2018)
Sea lettuce can be used as a functional green dye because it contains chlorophyll. Chlorophyll compounds as green coloring are obtained by extraction and stored in the form of encapsulation powder. This study has two purpose, there are to knowing the effect of the gelatin-maltodextrin encapsulant ratio on the encapsulates charagcteristics of sea lettuce functional coloring extract and determine the encapsulates comparison treatment of the best gelatin-maltodextrins in producing the characteritic encapsulates extract of sea lettuce functional coloring. Experiments in this study using a Randomized Single Factor Group with treatment ratio of gelatin and maltodextrin consisting of 9 levels, namely (1:0), (1:1), (1:1,5), (1:2), (1:2,5), (1:3), (1:3,5), (1:4), and (0:1). The results showed that the ratio of gelatin-maltodextrin was highly significant (P<0.01) on yield, total chlorophyll content, solubility, brightness level, significantly (P<0.05) on the level of redness (a*), yellowish level (b*) and no effect (P>0.05) on water content. The treatment of gelatin-maltodextrin 1:2,5 ratio is the best treatment to produce encapsulate sea lettuce extract with yield of 10.38%, water content of 8.61%, total chlorophyll content of 20.59 ppm, solubility of 0.80%, brightness level (L*) 45.21, redness level (a*) 1.68 and yellowish level (b*) 13.88. Keywords :Sea lettuce extract, gelatin, maltodextrin, encapsulation.